CO2 Emission Efficiency Measurement: Green Logistics Perspective - Fuad Selamzade; Ali Tehci; Yusuf Ersoy (Verimlilik Dergisi)
Purpose: This study aims to measure the carbon emission activities of Turkey, Azerbaijan, Kazakhstan, Kyrgyzstan and Uzbekistan and evaluate them from a green logistics perspective.Method: Within the scope of the research, efficiency analyses were conducted using the output-oriented Data Envelopment Analysis (DEA) constant returns to scale (CRS) model and the super efficiency CRS DEA model. The input and output variables used in the research were obtained from the World Bank website. Findings: In the research, the efficiency scores of the relevant countries were determined. It was determined that the efficiency scores of the countries were generally above 50%. The ranking of the efficient decision-making units among themselves was carried out with the super efficiency CRS DEA model. Some potential improvement suggestions were presented for the decision-making units that were not efficient. Originality: In order to leave a livable world to future generations, green energy production should be supported and Carbon Dioxide (CO2) emissions should be kept under control. Therefore, the efficiency assessment of countries' CO2 emissions is of vital importance. This study has an original feature because the CO2 emission activities of the Turkish Republics were carried out using the super efficiency CRS DEA model. This study can provide guidance to those who will conduct research on this subject and to country leaders.